2020
DOI: 10.1101/2020.03.26.010330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell type-specific histone acetylation profiling of Alzheimer’s Disease subjects and integration with genetics

Abstract: We profile genome-wide histone 3 lysine 27 acetylation (H3K27ac) of 3 major brain cell types from hippocampus and dorsolateral prefrontal cortex (dlPFC) of subjects with and without Alzheimer's Disease (AD). We confirm that single nucleotide polymorphisms (SNPs) associated with late onset AD (LOAD) prefer to reside in the microglial histone acetylome, which varies most strongly with age. We observe acetylation differences associated with AD pathology at 3,598 peaks, predominantly in an oligodendrocyte-enriched… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 95 publications
(123 reference statements)
3
7
1
Order By: Relevance
“…MVB12B has previously been identified as an AD risk gene 20 and forms part of an oligodendrocyte-enriched gene network in the AD brain 21 . These results are consistent with a previous study in which oligodendrocytes were reported to show the most widespread acetylation differences in the AD brain 22 . The top-ranked AD-hypoacetylated peak was annotated to multiple cell types, and located near NKAIN3 ( Supplementary Table 1 ), an AD GWAS candidate gene that has been shown to be differentially expressed in astrocyte subclusters 23 .…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…MVB12B has previously been identified as an AD risk gene 20 and forms part of an oligodendrocyte-enriched gene network in the AD brain 21 . These results are consistent with a previous study in which oligodendrocytes were reported to show the most widespread acetylation differences in the AD brain 22 . The top-ranked AD-hypoacetylated peak was annotated to multiple cell types, and located near NKAIN3 ( Supplementary Table 1 ), an AD GWAS candidate gene that has been shown to be differentially expressed in astrocyte subclusters 23 .…”
Section: Resultssupporting
confidence: 94%
“…Whereas epigenetic variation in late-stage AD predominantly points to oligodendrocytes, genetic risk points to microglia, suggesting independent biological mechanisms. Furthermore, our study corroborates the finding that genetic risk for AD is enriched at microglia-specific regulatory elements 4,22,48 and genes 35 . Additionally, we used CHAS to identify disease-associated pathways and transcription factors at cell type resolution.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prioritized SNPs in the MAPT-CRHR1 locus are genome-wide significant for 5 of the 7 addiction-associated traits (Extended Data Fig. 7-1 ), and the locus has been implicated in other neuropsychiatric traits, such as Alzheimer's disease ( Hoffman et al, 2019 ; Corces et al, 2020 ; Ramamurthy et al, 2020 ). We provide the summary of CNN predictions in these reported loci across all 14,790 analyzed SNPs along with the accompanying annotations that we incorporated into our prioritization of candidate causal SNPs and their predicted cell types (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial evidence supports a causal role for microglia and neuroinflammation in AD pathogenesis 29,60,61 . For example, many AD risk genes and genomic loci are most active in microglia 62–64 , and reactive microglia are thought to create a cytotoxic environment for neurons and exacerbate neurodegneration 6568 . Here, we provide evidence that neurons participate in this inflammatory signaling as well.…”
Section: Discussionmentioning
confidence: 99%